Hipertireoidismo em gato - Relato de caso - Léga, Elzylene; Pinto, Mildre Loraine; De Simone Sfrizo, Luciana [UNESP]; Do Nascimento Braz, Larissa Ayane [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Haraguchi, Greice; Chung, Denise Granato; Galvão, André Luiz Baptista [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2013)
Hyperthyroidism is the most common endocrine disease in cats middle-aged an older, it is a multisystemic metabolic disorder that results in elevated circulating of thyroid hormones, which consequently promote clinical manifestations due to increased basal metabolic rate. In Brazil the are few records of this disease. The objective of this paper is to describe a case of hyperthyroidism in cat, male, eight years old.
Hyperthyroidism in cat - Case report
Keywords: Erythrocytosis; Goiter; Thyroxine